IX Workshop on novel methods for electronic structure calculations - Gil Rebaza, Arles Víctor (2021)
Dear friends and colleagues, again this year as we have done every odd year since 2005 we are organizing the Workshop on Novel Methods for Electronic Structure Calculations, this time will be their 8th edition. The workshop will be dedicated to providing an up to date with the different mechanisms of calculation on materials, as well as the study of different materials. In general, during the workshop an intense exchange is targeted between speakers and participants. Always the relaxed atmosphere that has been generated at the meeting has allowed communication between speakers and participants, generating ideas for new lines of work, participation in projects, etc. As in the past it will be a great pleasure that you can participate in the workshop and a great joy that we can meet again or visit us first time. The workhsop will be held in the city of La Plata (Argentina), in the National University of La Plata, between the days 10th and 19th November.